Menolak Euforia atas Ketidakadilan: Tafsir Eksegesis 1 Korintus 13:6 dalam Tantangan Dunia Kontemporer - Sukma Hendra Wahyudi Surahman; Aji Suseno (JURNAL LUXNOS, 2026)
The main purpose of this article is to explore the ethical meaning of Paul’s statement in 1 Corinthians 13:6, “love does not rejoice in injustice,” and its relevance to the challenges of contemporary society. This study arises from the phenomenon of modern culture that often celebrates success rooted in unjust practices, whether in the political, economic, or digital sphere. This situation raises the question of how the biblical text can serve as a prophetic framework for evaluating and responding to such social realities. This research employs an exegetical method using a historical-grammatical approach, lexical analysis of the Greek terms chairein (“to rejoice”) and adikia (“injustice”), as well as contextual hermeneutics that connects the text with contemporary social praxis. The analysis also examines the rhetorical structure of 1 Corinthians 12–14 and relates it to the perspective of social theology concerning the relationship between love and justice. The findings reveal that Paul not only rejects personal satisfaction over the failures of others, but also criticizes collective euphoria rooted in structural injustice. According to Paul, genuine love directs joy toward truth that builds the faith community and restores communal life. This study emphasizes that love should not merely be understood as an interpersonal relationship, but also as a prophetic public ethic that resists the normalization of injustice. Ultimately, this article offers an understanding of love as a critical, transformative, and justice-oriented ethical-communal orientation within the context of the contemporary world